2019
DOI: 10.1111/gcb.14818
|View full text |Cite
|
Sign up to set email alerts
|

Selectively bred oysters can alter their biomineralization pathways, promoting resilience to environmental acidification

Abstract: Commercial shellfish aquaculture is vulnerable to the impacts of ocean acidification driven by increasing carbon dioxide (CO2) absorption by the ocean as well as to coastal acidification driven by land run off and rising sea level. These drivers of environmental acidification have deleterious effects on biomineralization. We investigated shell biomineralization of selectively bred and wild‐type families of the Sydney rock oyster Saccostrea glomerata in a study of oysters being farmed in estuaries at aquacultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 45 publications
1
29
1
Order By: Relevance
“…We also demonstrate such variation in abalone, with trait divergence indicated at the scale of populations within a single species. Our evidence suggests that in the case of abalone, traits enabling rapid growth show a negative correlation with traits needed for OA resistance during early development, in contrast to findings from commercially selected oysters in Australia ( 17 ). While it is unknown as to whether this relationship may hold true for other wild upwelling/nonupwelling populations, by selecting for rapid growers, aquaculture operators may inadvertently be selecting for genotypes vulnerable to OA.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…We also demonstrate such variation in abalone, with trait divergence indicated at the scale of populations within a single species. Our evidence suggests that in the case of abalone, traits enabling rapid growth show a negative correlation with traits needed for OA resistance during early development, in contrast to findings from commercially selected oysters in Australia ( 17 ). While it is unknown as to whether this relationship may hold true for other wild upwelling/nonupwelling populations, by selecting for rapid growers, aquaculture operators may inadvertently be selecting for genotypes vulnerable to OA.…”
Section: Discussioncontrasting
confidence: 82%
“…Significant uncertainty remains regarding how these sensitivities will affect shellfish production, especially since commercially cultured taxa show different vulnerabilities to OA ( 15 ). Variation in responses to OA is likely a complex function of differences in natural selection regimes ( 15 17 ), sensitivities among different early-life history stages ( 18 ), and in the nature and strength of transgenerational effects ( 19 ). As such, there is a critical need to understand how, and in which contexts, these factors contribute to OA impacts on molluscan seed production.…”
mentioning
confidence: 99%
“…As shown for S. glomerata , production of commercial bivalves that are more resilient to global change stressors, in tandem with advances from selective breeding efforts, hold promise in designing strategies for evolutionary rescue of key aquaculture resources to help climate proof shellfish industries. A better understanding of calcification physiology and mechanisms is needed, as recent studies show that this process is phenotypically plastic and can be adjusted with respect to environmental conditions (Fitzer et al, , , ; Zhao, Zhang, et al, ).…”
Section: Insights From Aquaculture Practice Via Epigenetic Selectionmentioning
confidence: 99%
“…An SEM-EBSD investigation of Mytilus galloprovincialis transplanted to a CO 2 vent (~pH = 7.2–7.8) revealed that they grew a thinner shell with disordered crystallography (Rodolfo-Metalpa et al ., 2011; Hahn et al ., 2012). This was also the case the shells of the oysters Magallana angulata (pH 7.2, 7.5) and M. hongkongensis (pH 7.3) grown in laboratory (CO 2 dosing) (Meng et al ., 2018, 2019), and Saccostrea glomerata farmed in coastal acidified environments (pH 7.6–7.8) (Fitzer et al ., 2018, 2019b). The disordered crystallography in S. glomerata wild type oysters grown in coastal acidified environments was as a result of altered biomineralisation pathways shown by changing shell carbon isotopes (Fitzer et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%